Effect of Neem Leaves Extract (Azadirachta Indica) on Wound Healing - Naveen Kumar Chundran; Ike Rostikawati Husen; Irra Rubianti (Althea Medical Journal, 2015)
Background: Neem leaves (Azadirachta Indica) have active ingredients such as nimbidin and sodium nimbidate which possess/possesinganti-inflammatory, antibacterial, antifungal and antiviral properties that help in healing process and also contains an excellent nutrition which plays/playing a vital role information of collagen and formation of new capillaries. The aim of this experimental study is to evaluate healing activity of neem leaves.Methods: This experiment was conducted in Pharmacology Lab of Universitas Padjadjaran on October 2012. Twenty seven rats were grouped randomly into 3 groups and 1.5cm of excision wound was created. Negative control group was treated with a topical application of saline solution (sodium chloride0.9%), treatment group with a topical application of neem leaves extract and positive control group had been treated with a topical application of povidone-iodine for 15 days. Healing was assessed by the longest diameter of the raw surface of wound on days 0, 5, 10 and 15. The data were then analyzed using Mann-Whitney U test.Results: There was a significant reduction in the longest diameter of wound in group of neem leaves extract, compared with group sodium chloride 0.9%,.and there was no significant difference in the longest diameter of wound between neem leaves, extract and povidone iodine. Conclusions: Neem leaves extract has the same wound healing rate compared to povidone iodine. A further study in human should be conducted in the future. [AMJ.2015;2(1):199–207]